High Color‐Rendering Index and Stable White Light‐Emitting Diodes by Assembling Two Broadband Emissive Self‐Trapped Excitons. Issue 2 (23rd November 2020) - Ma, Zhuangzhuang; Shi, Zhifeng; Yang, Dongwen; Li, Yawen; Zhang, Fei; Wang, Lintao; Chen, Xu; Wu, Di; Tian, Yongtao; Zhang, Yu; Zhang, Lijun; Li, Xinjian; et al.
Abstract: White light‐emitting diodes (WLEDs) are promising next‐generation solid‐state light sources. However, the commercialization route for WLED production suffers from challenges in terms of insufficient color‐rendering index (CRI), color instability, and incorporation of rare‐earth elements. Herein, a new two‐component strategy is developed by assembling two broadband emissive materials with self‐trapped excitons (STEs) for high CRI and stable WLEDs. The strategy addresses effectively the challenging issues facing current WLEDs. Based on first‐principles thermodynamic calculations, copper‐based ternary halides composites, CsCu2 I3 @Cs3 Cu2 I5, are synthesized by a facile one‐step solution approach. The composites exhibit an ideal white‐light emission with a cold/warm white‐light tuning and a robust stability against heat, ultraviolet light, and environmental oxygen/moisture. A series of cold/warm tunable WLEDs is demonstrated with a maximum luminance of 145 cd m −2 and an external quantum efficiency of 0.15%, and a record high CRI of 91.6 is achieved, which is the highest value for lead‐free WLEDs. Importantly, the fabricated device demonstrates an excellent operation stability in a continuous current mode, exhibiting a long half‐lifetime of 238.5 min. The results promise the use of the hybrids of STEs‐derived broadband emissive materials for high‐performance WLEDs. Abstract : Stable and highly luminescent CsCu2 I3 @Cs3 Cu2 I5 composites are synthesized through a one‐step spin‐coating method. They exhibit white‐light emission through self‐trapped excitons, as well as cold/warm white‐light tuning. By using the composites as a white‐light emitter, electrically driven cold/warm tunable WLEDs with a record color‐rendering index of 91.6 are successfully demonstrated, and a long half‐lifetime of 238.5 min is achieved.